HER2 prognostic values in non-muscle-invasive bladder cancer: a step towards personalized treatment for BCG instillation - Xinpei Deng; Runhao Zheng; Xingliang Tan; Kai Yao (Discover Oncology)
Abstract This comment discusses the findings of a study on the prognostic significance of HER2 expression in high-risk non-muscle-invasive bladder cancer (NMIBC) patients treated with Bacillus Calmette-Guérin (BCG) therapy. The study highlights that high HER2 expression is an independent predictor of BCG failure and poor recurrence-free survival. The comment underscores the potential of HER2 as a biomarker for tailoring treatment strategies in NMIBC, particularly for patients with high HER2 expression, who may benefit from more aggressive or targeted therapies. It also calls for further validation of HER2-targeted therapies and the need for personalized treatment approaches to improve clinical outcomes in high-risk NMIBC patients.